Электронный курс: разработка мультимедиа учебных материалов (СО): электронный курс - Ситникова О. В. Оксана Валерьевна; Решетникова С. Л. Светлана Леонидовна; Лобаненко О. Б. Ольга Борисовна; Ряшенцев И. В. Игорь Владимирович (Томск, TPU Moodle, 2017)
Заглавие с экрана